Adoption of digital technologies for future construction project - Yusoff, Adam Syamil (2024)
The adoption of digital technology in construction projects is transforming the construction sector through improving efficiency, accuracy, and collaboration. However, there are few issues regarding the adoption of digital technologies in construction projects such as lack of skills and training, reluctant to change, and lack of awareness on digital technologies. These issues not only impeded the construction growth, but at the same time discourage new generation to step forward in implementing digital technologies in construction projects. Therefore, the aim of this research is to suggest effective approaches for encouraging the integration of digital technology in construction projects, alongside the goal of enhancing project performance. The first objective of this research is to identify the level of readiness among construction participants. Second, to determine factors influencing the adoption of digital technologies, and the last objective is to propose key strategies to foster the adoption of digital technologies in construction project. Quantitative methods had been used and in order to achieve the research objectives, data collections from 107 respondents out of 247 respondents of contractor grade G6 and G7 within Klang Valley were gathered through questionnaire survey method and the secondary data were obtained from the written resources and internet. Then, the raw data was analysed by using the Statistical Package for Social Science (SPSS) version 29 software. From the findings, it was found that most of the respondents were prepare well known about digital construction, however there were certain negative factor influence the implementation digital construction such as lack of skill workers and high cost. Besides, strategy in promoting the digital construction were suggested to encourage the adoption of digitalization in construction project. To sum up, the author also recommended broadening the scope of the research beside contractor grade G6 and G7. The interview method also had been recommended to prevent misunderstanding during the data collection.